A benefits framework for public access ICT4D programmes. Issue 2 (28th October 2019) - Uys, Corrie; Pather, Shaun
Abstract: There have been expectations across the developing world that information and communications technologies (ICTs) will deliver benefits to marginalised people. Despite many programmes related to the promotion of Internet uptake and usage amongst poorer communities, evidence regarding such benefit is lacking, and there is little agreement in respect of frameworks and metrics to evaluate the benefits thereof. This paper reports on a case study that investigated the nature of a public access information and communication technologies for development (ICT4D) programme and presents a framework for assessing the associated benefits in the South African context. The capability approach is used as a lens to assess the process of providing opportunities to ordinary citizens through ICT access and use. By operationalising agency and conversion factors, the study identified inhibitors and enhancers of opportunities and choices in realising benefits. Through the application of a critical realism paradigm and a mixed method analytical approach, perceptions of a changed life, aspirations for a better life, and "hope" emerged as key intangible benefits. The paper presents an ICT benefits framework, which serves as an important contribution to the ICT4D evaluation field. A novel outcome of the study is that it provides evidence of constructs that to date have been considered as intangible benefits in the literature.